On the Take : How Medicine's Complicity with Big Business Can Endanger Your Health. - Kassirer, Jerome P. (Oxford University Press, 2004)
We all know that doctors accept gifts from drug companies, ranging from pens and coffee mugs to free vacations at luxurious resorts. But as the former Editor-in-Chief of The New England Journal of Medicine reveals in this shocking expose, these innocuous-seeming gifts are just the tip of aniceberg that is distorting the practice of medicine and jeopardizing the health of millions of Americans today. In On the Take, Dr. Jerome Kassirer offers an unsettling look at the pervasive payoffs that physicians take from big drug companies and other medical suppliers, arguing that the billion-dollar o.